Major Classes of Phytonutriceuticals in Vegetables and Health Benefits: A Review - Dias, João Silva (Journal of Nutritional Therapeutics, 2012)
Vegetables are essential for well-balanced diets since they supply phytonutriceuticals. About 3 billion people in the world are malnourished due to imbalanced diets. Regular consumption of a vegetable rich diet has undeniable effects on health since they have been strongly associated with improvement of gastrointestinal health, good vision, and reduced risk of heart disease, stroke, chronic diseases such as diabetes, and some forms of cancer. The mechanism by which vegetables decrease risk of disease is complex and largely unknown. Some phytochemicals of vegetables are strong antioxidants and are thought to reduce the risk of chronic disease by protecting against free radical damage, by modifying metabolic activation and detoxification of carcinogens, or even by influencing processes that alter the course of tumor cells. The dietary fiber content and type of different vegetables may also contribute to the overall health benefit. Each vegetable contains a unique combination of phytonutriceuticals. A great diversity of vegetables should be eaten to ensure that individual’s diet includes a combination of phytonutriceuticals and to get all the health benefits.